Goodyera R.Br. - Chinchilla Alvarado, Isler Fabián (2022)
The genus Goodyera was named in 1813 by leading Scottish botanist Robert Brown, who was director of the botany department of the British Museum, and president of the Linnaean Society of London. The name honors the English botanist John Goodyer. Brown (1813) based the genus on Goodyera repens, which grows in the temperate and boreal Northern Hemisphere.